2018
DOI: 10.3897/zse.94.25189
|View full text |Cite
|
Sign up to set email alerts
|

New populations of two threatened species of Alsodes (Anura, Alsodidae) reveal the scarce biogeographic knowledge of the genus in the Andes of central Chile

Abstract: High Andean environments of central Chile (32°–38°S) are inhabited by several endemic species of the genus Alsodes. Two of them, A.pehuenche and A.hugoi, have geographic distributions restricted to their type locality and surroundings. The Chilean government classifies A.pehuenche as Critically Endangered (like the IUCN) and A.hugoi as Vulnerable. In this study we report 16 new localities of Alsodes, corresponding to first order streams, located in the Andes of Chile between 35°58’ and 36°32’S (1800–2470 m). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…We suggest that the IUCN Red List of Threatened Species (Avila 2016) should be updated with information from Mella et al (2018) and our publication. Our work, and other recent studies that expand the geographic distribution of Chilean species, such as Alsodes hugoi Cuevas & Formas, 2001(Correa et al 2018, Diplo laemus darwinii , and Alsodes verrucosus (Philippi, 1902) (Mella-Romero and Lamilla-Maulén 2019), emphasize the need of more extensive and intensive herpetological sampling, especially along the border with Argentina (e.g., Patagonian steppe). This will allow for the real geographic distributions of a great number of Chile's reptiles and amphibians to be better determined.…”
Section: Discussionsupporting
confidence: 67%
“…We suggest that the IUCN Red List of Threatened Species (Avila 2016) should be updated with information from Mella et al (2018) and our publication. Our work, and other recent studies that expand the geographic distribution of Chilean species, such as Alsodes hugoi Cuevas & Formas, 2001(Correa et al 2018, Diplo laemus darwinii , and Alsodes verrucosus (Philippi, 1902) (Mella-Romero and Lamilla-Maulén 2019), emphasize the need of more extensive and intensive herpetological sampling, especially along the border with Argentina (e.g., Patagonian steppe). This will allow for the real geographic distributions of a great number of Chile's reptiles and amphibians to be better determined.…”
Section: Discussionsupporting
confidence: 67%
“…Alsodes hugoi Cuevas y Formas 2001: Cuevas y Formas (2001) describen esta especie en la localidad de Vilches Alto, en las cercanías a la RNAL, pero Araya y Cisternas ( 2008) la mencionan por primera vez en la RNAL. Por último, existe un nuevo trabajo que documenta por primera vez su presencia fuera de la comuna de San Clemente, aumentando su rango de distribución 100 KM al sur (Correa et al 2018).…”
Section: Resultsunclassified
“…Alsodes pehuenche Cei, 1976 (Anura, Alsodidae) is a species that inhabits the Andean wetlands of Argentina and Chile, which shows a very narrow geographical distribution range and a very high level of endemism (Corbalán et al 2008(Corbalán et al , 2014Correa et al 2013Correa et al , 2018. Furthermore, it is categorized as "Critically Endangered" (CR) according to the criteria of IUCN SSC Amphibian Specialist Group (2019), since this anuran and its habitat are faced with multiple threats, such as: the paving of the CH-115 international highway, the contaminant particulate material of vehicles, and the impact of domestic livestock trampling, domestic tourism waste and the change in hydrological cycles resulting from climate change (Corbalán et al 2010;Correa et al 2013;Lobos et al 2018); the use of salts to snowmelt during the winter (Corbalán et al 2014); and the confirmed presence of the chytrid fungus (Bd) in frogs caught in Chilean streams, adjacent to the localities of the border crossing "Paso Internacional Pehuenche", Laguna del Maule and Lo Aguirre (Dayana Vásquez pers.…”
mentioning
confidence: 99%